2019
DOI: 10.1016/j.jtho.2019.06.009
|View full text |Cite
|
Sign up to set email alerts
|

MET IHC Is a Poor Screen for MET Amplification or MET Exon 14 Mutations in Lung Adenocarcinomas: Data from a Tri-Institutional Cohort of the Lung Cancer Mutation Consortium

Abstract: Introduction: MNNG HOS Transforming gene (MET) amplification and MET exon 14 (METex14) alterations in lung cancers affect sensitivity to MET proto-oncogene, receptor tyrosine kinase (MET [also known by the alias hepatocyte growth factor receptor]) inhibitors. Fluorescence in situ hybridization (FISH), next-generation sequencing (NGS), and immunohistochemistry (IHC) have been used to evaluate MET dependency. Here, we have determined the association of MET IHC with METex14 mutations and MET amplification. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(87 citation statements)
references
References 18 publications
0
86
0
1
Order By: Relevance
“…They combined NGS with FLA, so probably no MET exon 14 skipping mutations were missed and indeed the prevalence of 2.2% is in accordance with current literature (7,14). While 2 patients is a small number to base firm conclusions on, Guo et al performed a similar study in 2019 and they came to the same conclusion as Baldacci et al: MET IHC is not suitable as a screening tool to detect MET exon 14 skipping mutations (15). In 2018, Lambros et al also described MET IHC as a very weak tool for screening purposes and they report that MET IHC might even decrease the probability of predicting MET exon 14 skipping mutations in a multiclass model (16).…”
Section: Editorial Commentarymentioning
confidence: 53%
“…They combined NGS with FLA, so probably no MET exon 14 skipping mutations were missed and indeed the prevalence of 2.2% is in accordance with current literature (7,14). While 2 patients is a small number to base firm conclusions on, Guo et al performed a similar study in 2019 and they came to the same conclusion as Baldacci et al: MET IHC is not suitable as a screening tool to detect MET exon 14 skipping mutations (15). In 2018, Lambros et al also described MET IHC as a very weak tool for screening purposes and they report that MET IHC might even decrease the probability of predicting MET exon 14 skipping mutations in a multiclass model (16).…”
Section: Editorial Commentarymentioning
confidence: 53%
“…24 Several studies have shown MET IHC overexpression poorly predicts for the presence of METex14 alterations. [25][26][27] Furthermore, there may be a high degree of inter-observer variability in the interpretation of IHC. 28 As such, most of the assays for METex14 involve molecular techniques ( Figure 2).…”
Section: Molecular Diagnostic Approaches For Metex14 Skipping Alteratmentioning
confidence: 99%
“…Consequently, MET overexpression is expected to be strongly associated with MET alterations. However, MET overexpression does not always accompany MET amplification or METex14 in lung cancers [19]. Here, we investigated the association between MET overexpression and the MET alterations in sGBM.…”
Section: Figurementioning
confidence: 99%